T peripheral helper cells in autoimmune diseases: What do we know? - Huang, Yao; Ba, Xin; Han, Liang; Wang, Hui; Lin, Weiji; Chen, Zhe; Tu, Shenghao (Frontiers in Immunology, 2023)
The interactions between T cells and B cells are essential for antibody responses and the development of autoimmune diseases. Recently, a distinct subset of T cells capable of helping B cells was established in synovial fluid, and they were termed peripheral helper T (Tph) cells. PD-1hiCXCR5−CD4+ Tph cells express high levels of CXCL13, which drives the formation of lymphoid aggregates and tertiary lymphoid structures, ultimately facilitating the local production of pathogenic autoantibodies. Tph and T follicular helper cells share some key features but can be distinguished by their surface markers, transcriptional regulation, and migration capability. We summarize recent findings on Tph cells in this review and provide a perspective on their potential roles in a range of autoimmune diseases. More clinical and in-depth mechanistic investigations of Tph cells may help to improve the understanding of pathogenesis and further provide novel therapeutic targets in autoimmune diseases.